2014
DOI: 10.1002/smll.201470099
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials: Structure of Single‐Wall Carbon Nanotubes: A Graphene Helix (Small 16/2014)

Abstract: Single‐walled carbon nanotubes (SWCNTs) are formed by J.‐K. Lee et al. from the spiral growth of graphene nanoribbons like an ivy vine growing on a tree. On page 3283, the helical structure addresses mounting inconsistencies in the measured mechanical and electrical properties of SWCNTs. The growth and material properties, including chirality, need to be re‐interpreted in terms of non‐idealised structures of SWCNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…US has also been used to study the interaction between other polymers, such as epoxy resins and proteins, with different types of organic and inorganic surfaces. [ 48‐51 ] Many of those studies involved the interaction of a molecule of non‐trivial size with a surface. Due to their high conformational degrees of freedom, a fairly large amount of computation (scriptOfalse(102false)$\mathcal {O}(10^2)$ to scriptOfalse(103false)$\mathcal {O}(10^3)$ ns) was typically used for each PMF profile.…”
Section: Introductionmentioning
confidence: 99%
“…US has also been used to study the interaction between other polymers, such as epoxy resins and proteins, with different types of organic and inorganic surfaces. [ 48‐51 ] Many of those studies involved the interaction of a molecule of non‐trivial size with a surface. Due to their high conformational degrees of freedom, a fairly large amount of computation (scriptOfalse(102false)$\mathcal {O}(10^2)$ to scriptOfalse(103false)$\mathcal {O}(10^3)$ ns) was typically used for each PMF profile.…”
Section: Introductionmentioning
confidence: 99%
“…While the anionic and cationic liposomal NPs were revealed to attract the proteins with specific isoelectric point (p I ) range, [ 7 ] many investigations showed that the protein binding is independent of the charged functional groups and the p I of proteins. [ 8,9 ] One typical example is rapid adsorption of anionic plasma proteins onto both carboxylate and ammonium functionalized NP surfaces irrespective of their charges. [ 10 ] The same is true for the cellular responses; protein corona was reported to facilitate the association of positively charged NPs with cells, [ 11 ] while it was revealed that the serum proteins on the surface of anionic gold NPs induce a stronger affinity to the supported lipid bilayers, as compared to the cationic ones.…”
Section: Introductionmentioning
confidence: 99%